Fair and foul beyond the myths and paradoxes of sport - Eitzen, D. Stanley (Lanham ROWMAN & LITTLEFIELD, 2016)
Fair and Foul explores our loves of sport, just as it reveals sport's darker side-the influence of big business, corruption, price gouging, political maneuvering, gender bias, media control, and more. The sixth edition features a new chapter on mass media and sport, a revised chapter on college sport that asks whether big-time college sports are compatible with higher education. This edition also features new material throughout, such as the rising costs and increasing injuries in youth sports, fantasy sports, homophobia in sport, "one and done", and more. Fair and Foul draws on examples ranging from youth to pro sports to give us a deeper understanding of how to shape our everyday world. Ideal for sparking classroom discussion, Fair and Foul is an excellent book for students of sports and society, American culture, and other courses
1. The duality of sport -- 2. Sport unites, sport divides -- 3. Names, logos, mascots, and flags: The contradictory uses of sports symbols -- 4. Sport is fair, sport is foul -- 5. Sport is healthy, sport is destructive -- 6. The organization of youth sport: Issues and consequences -- 7. Sport is expressive, sport is controlled -- 8. Are sports played on a level playing field? Issues of race, class, and gender -- 9. The mass media and sport: Distorted windows, blinders, and game changers -- 10. Big-time college sports: Commercialized sport within academia -- 11. Sport as the path to success? Myth and reality -- 12. Professional sports franchises: Public teams, private businesses -- 13. The globalization of sport -- 14. The challenge: Changing sport.
Includes bibliographical references and index
Keywords: Sports -- Psychological aspects; Sports -- Sociological aspects; Sports -- Social aspects -- United States